Iktiofauna di perairan hutan tropis dataran rendah, Hutan Harapan Jambi [Ichthyofauna of lowland rainforest waters, Harapan Rainforest, Jambi] - Tedjo Sukmono; Dedy Duryadi Solihin; M. F. Rahardjo (Jurnal Iktiologi Indonesia, 2013)
Harapan Rainforest Jambi, the first restoration ecosystem area on lowland rainforest in Indonesia, has various types of aquatic ecosystem. Research was conducted in September 2012 to July 2013 aimed to assess the diversity of freshwater fish species that naturally exist in Harapan rainforest. Fish sampling conducted on eight water bodies in the area of Harapan Rainforest base on different habitat typology by using nets, gill nets, scoop net, traditional trap, and fishhook. The results showed the diversity of fish in the Harapan Rainforest consisting of 123 fish species, 25 families, and 52 genera. Cyprinidae has much species (59 species of fish). Based on the category of IUCN Red List conservation status of fish in the Harapan Rainforest are divided into 5 categories: not evaluated 74 species, data deficient 4 species, least concern 41 species, nearly threatened 3 species, and endangered 1species. Abstrak Hutan Harapan Jambi merupakan kawasan restorasi ekosistem pada areal hutan hujan tropis dataran rendah pertama di Indonesia, memiliki berbagai tipe ekosistem perairan. Penelitian dilakukan pada bulan September 2012 hingga Juli 2013 bertujuan untuk mengkaji keanekaragaman spesies ikan air tawar alami yang ada di areal tersebut. Pengambilan contoh ikan dilakukan pada delapan badan air di areal Hutan Harapan berdasarkan tipologi habitat menggunakan jala, jaring insang, sudu, serok, seruau, bubu dan pancing. Hasil penelitian menunjukkan keanekaragaman ikan di Hutan Harapan terdiri atas 123 spesies ikan, 25 famili, dan 52 genera. Famili Cyprinidae mempunyai spesies terbanyak (59 spesies). Berdasarkan kategori status konservasi IUCN Red List ikan di Hutan Harapan terbagi atas lima kategori yaitu: belum dievaluasi 74 spesies, informasi kurang 4 spesies, berisiko rendah 41 spesies, hampir terancam 3 spesies, dan genting 1 spesies.